Effects of Ta doping and irradiation with He+ ions on photoluminescence of MgAl2O4 spinel ceramics. Issue 8 (July 2020) - Spiridigliozzi, H.; Pille, A.; Schoenstein, F.; Museur, L.; Feldbach, E.; Mändar, H.; Kitaura, M.; Kanaev, A.
Abstract: Photoluminescence (PL) properties of pristine and Ta-doped MgAl2 O4 spinel ceramics prepared via spark plasma sintering technique and irradiated with He + ions were studied. The results indicate strong influence of the grain boundaries on PL spectra. Ta doping promotes the formation of O and Al vacancies at the grain boundaries leading to an increased number density of F + centres. The ionised irradiation forms antisites preferentially at the grain boundaries, which inhibit excitonic PL and exciton energy transfer while do not affect proper PL of lattice defects. A weak PL excitation band at 7.25 ± 0.25 eV may belong to excitons localised near bulk antisites. In the Ta-doped ceramics, the electronic transitions between 5.75 eV and 7.0 eV belong to an intermediate state situated at the grain boundaries and structurally linked to Ta, which readily transfers energy to F and F + centres; it was assigned to the nucleated Mg4 Ta2 O9 phase.